Corticosteroid and antibiotic use in hospitalized patients in Lebanon with acute exacerbation of chronic obstructive pulmonary disease - S. Basma; A. Al-Hajje; P. Salameh; I. Nader; AM. Henaine (SpringerOpen, 2023)
Abstract Background Chronic obstructive pulmonary disease (COPD) is currently one of the leading causes of death worldwide, with 90% of these deaths reported in low- and middle-income countries. In Lebanon, the prevalence of COPD is 9.7%. The Global Initiative for Chronic Obstructive Lung Disease (GOLD) recommends the use of antibiotics and corticosteroids in inpatients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD). The studies examining the level of conformity with the GOLD recommendations are rare, which increases the need for the current study. Methods A 3-month cross-sectional study was done. Patients included were those diagnosed with acute exacerbations of COPD and admitted to one of the selected hospitals in Beirut, of various nationalities and sexes, aged 18 to 89. Data were selected from patient files admitted between January 2020 and June 2022 using a data collection sheet. The SPSS version 24 statistics software was used to conduct statistical analysis. Results A total of 260 patients were recruited, with 86.7% receiving systemic corticosteroids, 24.3% respecting dose, and 81.8% respecting the appropriate duration of corticosteroid intake. 80% exhibited pulmonary indications for receiving antibiotics, and 56.53% had the necessary cardinal symptoms. Around 74.5% of patients use antibiotics for the recommended time of 5 to 7 days. Age (p value = 0.006), gender (p value = 0.049), alcohol consumption (p value = 0.018), and use of psychiatric medications (p value = 0.049) are correlated with the conformity index of corticosteroid administration. A correlation was observed between the duration of use of antibiotics with cardinal symptoms (p value = 0.003), CRP-value (p value = 0.007), and type of hospital (p value = 0.00). Conclusion This investigation revealed a need for correction in a deviation from the guidelines, shed light on existing clinical procedures, and emphasized the growing concern about the uncontrollable rate of antibiotic use and inadequate corticosteroid dosing.